Legal Formulation of Substitute Money Charges in Corruption Cases in the Perspective of State Financial Recovery - Sari, Amalia; Santiago, Faisal (Greenation Publisher & Yayasan Global Resarch National, 2025)
The responsibility for corruption lies with the perpetrator, and the state is only responsible for execution without bearing the shortfall, meaning that losses may not be fully recovered. Consequently, further elucidation is requisite on Article 18 paragraph 1 letter b of the Corruption Eradication Law with regard to the imposition of restitution. The present study aims to examine the mechanism for recovering state financial losses, including the limitations in recovering losses that are not enjoyed by the perpetrators of corruption crimes and the legal construction of restitution in corruption cases from the perspective of restoring state finances. The research method employed is a normative research method through a statutory approach and an analytical approach. The results obtained demonstrate that the mechanism for recovering state losses due to corruption offences still faces obstacles. The provisions of Article 18 paragraph (1) letter b of the Corruption Eradication Law do not provide adequate legal certainty regarding the imposition of restitution in the perspective of state financial recovery. It is therefore recommended that a reformation of legal provisions, especially those pertaining to the imposition of restitution, is initiated with a view to clarifying the limits of the perpetrator's responsibility and thereby enhancing the effectiveness of state financial recovery in cases of corruption offences.